Viability and effectiveness of the general system of royalties today (2019)
This document presents a report as a critical essay on the territorial participation of the Colombian State through the General System of Royalties SGR at present. Within the trial, key elements were taken into account such as the recognition, definition, scope, legislation, logistics and viability of this entity at the regional or national level, through a rigorous analysis on which are the procedures exercised by the SRG as a decentralized entity present in all the territories of the country, identifying if the management policies of the entity are met or not under the provisions stipulated in each execution period and investigating how effective and equitable may be the allocation, distribution, goals, significant experiences, administration, execution, control, proper use and allocation of budget amounts or profits from the exploitation of non-renewable natural resources immersed in Colombian territory in recent years.